What Are Nutrient-Dense Fish Feeds and Their Importance in Aquaculture? - Richard D. Miles; Frank A. Chapman (EDIS, 2007)
FA-145, a 4-page fact sheet by Richard D. Miles and Frank A. Chapman, describes the key nutrition concepts in aquaculture, the role of nutrient-dense feed in animal performance and environmental water quality, and the potential for improved feed manufacturing technology improve the profitability and sustainability of the aquaculture industry. Published by the UF Department of Fisheries and Aquatic Sciences, March 2007.